Living on the Margin : An Archaeology of a Swedish Roma Camp - Monié Nordin, Jonas ; 0009-0009-2695-2265; Fernstål, Lotta; Hyltén-Cavallius, Charlotte (World Archaeology, 2022)
In 1959, the politics of assimilation led to the creation of a set of municipally organised camps for Roma people in the Stockholm area. The camps were to function as controlled settlements of transition for Roma families awaiting proper homes. This paper focuses on one such camp – the Skarpnäck Camp – which existed longer than anticipated, to the point that its continued operation was criticised as being inconsistent with the government’s assimilation policy. This paper represents an analysis of historical archaeological fieldwork at the former Skarpnäck Camp in southern Stockholm and is based upon interviews conducted with former inhabitants of and visitors to the camp. It uncovers aspects of Roma history on the margins of Swedish society and how marginalisation of the Roma group was given physical form in the creation of sanctioned camps.
Keywords: Roma people; camps; assimilation; Sweden; modernity